Productivity and Profitability of Elephant Foot Yam Grown under Multilayer Vegetable Growing System - SINGH, RAJPAL (JOURNAL OF ROOT CROPS, 2015)
Field experiments were conducted during the year 2010 . 11 and 2011 . 12 to assess the yield and economics of elephant foot yam sown with bottle gourd, ridge gourd and bitter gourd under multilayer vegetable cropping system. The yield of corms (376.07 q/ha) was observed highest in the sole crop of elephant foot yam followed by elephant foot yam + bitter gourd while the maximum net return (Rs. 377673/ha) and income per rupee investment (2.17) was observed in the elephant foot yam when it was grown with bitter gourd. The results clearly indicated that the vegetable bitter gourd can be profitably intercropped with the elephant foot yam.